2014
DOI: 10.1136/bmjopen-2014-006710
|View full text |Cite
|
Sign up to set email alerts
|

Population-based cohort study on the risk of pneumonia in patients with non-traumatic intracranial haemorrhage who use proton pump inhibitors

Abstract: ObjectivesThis nationwide cohort study investigated the association between proton pump inhibitor (PPI) usage and the risk of pneumonia in patients with non-traumatic intracranial haemorrhage (ICH).DesignNationwide population-based cohort study.SettingLongitudinal Health Insurance Database 2010 (LHID2010) sampled from the Taiwan National Health Insurance Research Database.Participants4644 patients with non-traumatic ICH from 2010 to 2011 were identified. Patients aged <18 years and newly diagnosed with non-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Previous studies conducted using the NHIRD have shown that patients with stroke [ 13 ] or COPD [ 14 , 15 ] have non-significant risk of pneumonia. By contrast, PPI use in individuals with nontraumatic intracranial hemorrhage was at a high risk of long-term pneumonia [ 16 ]. Therefore, the association between PPI use and long-term risk of pneumonia was not well established.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted using the NHIRD have shown that patients with stroke [ 13 ] or COPD [ 14 , 15 ] have non-significant risk of pneumonia. By contrast, PPI use in individuals with nontraumatic intracranial hemorrhage was at a high risk of long-term pneumonia [ 16 ]. Therefore, the association between PPI use and long-term risk of pneumonia was not well established.…”
Section: Discussionmentioning
confidence: 99%
“…For research purposes, a subset of database, namely, the Longitudinal Health Insurance Database 2010 (LHID2010), was provided by the National Health Research Institutes, and it had been implemented in numerous research articles. (Chang et al 2015;Chou et al 2015;Ho et al 2014;Wu et al 2014) This dataset contains of one million individuals chosen randomly from the NHIRD at the year 2010 and contains medical information from January 1997 to December 2013 of each subject under the coverage. The Catastrophic Illness Registry Data file was supplemented for identification of deaths during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that proton pump inhibitors (PPIs) are positively associated with the risk of community-acquired pneumonia (CAP) for various disease and age populations [3][4][5][6][7][8] , but the letter mentioned, "The author of the manuscript has not clearly described or validated the swallowing test in these dementia patients. Swallowing problems are the one of most common causes of pneumonia.…”
Section: Reply To: Proton Pump Inhibitors and Risk Of Pneumonia In Inmentioning
confidence: 99%